2019
DOI: 10.1177/0898010119874971
|View full text |Cite
|
Sign up to set email alerts
|

The Emergency Resiliency Initiative: A Pilot Mindfulness Intervention Program

Abstract: Purpose: To assess the feasibility of a pilot mindfulness intervention program, the Emergency Resiliency Initiative (ERI), as well as to investigate changes in burnout scores and key drivers to burnout among registered nurses (RNs) and patient care technicians (PCTs) in a Level 1 trauma center emergency department (ED). Design: A mixed methods pre/post study with data collection points before and after the 3-month intervention. Method: Three mindfulness educational/experiential sessions were delivered once a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…While many recent studies report on particular HCW well-being behaviors in relation to resilience or burnout (Adair et al, 2020a; Alexander et al, 2015; Gauthier et al, 2015; Goodman & Schorling, 2012; Guo et al, 2018; Mealer et al, 2014; Muir & Keim-Malpass, 2020; Oskrochi et al, 2016; Shanafelt et al, 2005, 2012; Thompson et al, 2016; van der Riet et al, 2018; Wang et al, 2018; West et al, 2016; Yang et al, 2018), limited research has been conducted on the association between the total number of well-being behaviors and resilience among HCWs. This study contributes to the literature by providing evidence that engaging in more well-being behaviors is associated with increased emotional thriving and emotional recovery, which are domains of resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many recent studies report on particular HCW well-being behaviors in relation to resilience or burnout (Adair et al, 2020a; Alexander et al, 2015; Gauthier et al, 2015; Goodman & Schorling, 2012; Guo et al, 2018; Mealer et al, 2014; Muir & Keim-Malpass, 2020; Oskrochi et al, 2016; Shanafelt et al, 2005, 2012; Thompson et al, 2016; van der Riet et al, 2018; Wang et al, 2018; West et al, 2016; Yang et al, 2018), limited research has been conducted on the association between the total number of well-being behaviors and resilience among HCWs. This study contributes to the literature by providing evidence that engaging in more well-being behaviors is associated with increased emotional thriving and emotional recovery, which are domains of resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in well-being behaviors may be one such individual level strategy that theoretically may fuel the process of resilience and strengthen resilience capacity (Szanton & Gill, 2010). Research has demonstrated that well-being behaviors such as exercise (Guo et al, 2018; Oskrochi et al, 2016; Shanafelt et al, 2012; Yang et al, 2018), relationships with family and friends (Rippstein-Leuenberger et al, 2017; Thompson et al, 2016; Wang et al, 2018), meditation (Gauthier et al, 2015; Goodman & Schorling, 2012; Muir & Keim-Malpass, 2020; van der Riet et al, 2018), yoga (Alexander et al, 2015), going on vacations (Shanafelt et al, 2012), and reflecting on the positive things in life (Sexton & Adair, 2019) are associated with lower burnout or higher resilience. Current research often assesses well-being behaviors separately from one another (Cleary et al, 2018; Joyce et al, 2018) or with focus on certain HCW groups (Lebensohn et al, 2013; Shanafelt et al, 2012).…”
mentioning
confidence: 99%
“…Authors reported saturation effect or lack of lulls between changes can lead to change fatigue (Brown et al, 2018; McMillan & Perron, 2020b). Authors described an intensification of workload results in a blitz of change initiatives, in which staff are expected to alter their practice and implement the changes with a lack of resources (Muir & Keim‐Malpas, 2020; Vestal, 2013). In a cross‐sectional study, healthcare teams who faced constant change but lacked the ability to make or sustain change, known as adaptive reserve, experienced change fatigue (Huynh et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors recognized nurses are not immune to the effects of constant change (Brown & Abuatiq, 2020; Davis, 2002). Most concerning, the impact of change places significant pressure on nurses to carry out changes with a lack of accompanying support (Davis, 2002; McMillan & Perron, 2013; Muir & Keim‐Malpas, 2020; Vestal, 2013). For example, a qualitative study participant reported feeling stressed, insecure, and anxious about the new changes expected in practice (Muir et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…ahasiswa dapat melakukan mindfulness untuk memperbaiki emotion regulation dengan cara meningkatkan awareness (Erisman & Roemer, 2010 dalam (Hill & Updegraff, 2012)). Latihan mindfulness dapat menjadi metode praktikal untuk mengurangi burnout serta meningkatkan resiliensi dan well-being (Muir & Keim-Malpass, 2020). Dalam meningkatkan kemampuan realistic optimism intervensi yang dapat digunakan contohnya seperti Best Possible Self intervention dan latihan selfcompassion (Malouff & Schutte, 2017).…”
Section: Pembahasanunclassified